Performance Analysis of a Dc-Dc Multilevel Boost Converter - Julakanti, Santhosh Reddy (My University, 2017)
The core contribution in this thesis is mathematical, simulation and experimental analysis of a DC-DC multilevel boost converter (MBC). MBC is derived from the conventional boost converter by adding 2N-1 capacitors, 2N-1 diodes, with on driven switch and one inductor without changing the main conventional boost converter, to obtain N levels of output voltage. The proposed topology is a non-isolating circuit operated at high switching frequency.As a result the size of inductor and capacitor as well as ripple across it reduces. The structure of the circuit is multimodular to convert low input dc voltage to high output dc voltage with low rating devices at low duty cycle. This marks the circuit more suitable for various applications as Photovoltaic (PV) system, fuel cell etc. The open loop and closed loop analysis of the converter is done. A detailed mathematical analysis to select suitable value of Inductor and capacitor to meet output requirement is given. Non-linear dynamic analysis of full order MBC, reduced order MBC and small signal modeling of the converter is presented. To verify the mathematical results, simulations are done in Matlab Simulink. Finally, to demonstrate the validity of proposed theory and simulation results, a prototype was developed in the lab.
Master of Engineering -Power Systems
Keywords: Multilevel Boost converter (MBC); PV system; Multilevel Inverters (MLIs); Pulse width modulation (PWM)